STRENGTHENING COMMUNITY CAPACITY TO BOOST IMMUNITY DURING THE COVID-19 PANDEMIC - Bambang Aditya Nugraha Bambang Aditya Nugraha; Sulastini Sulastini; Sandra Pebrianti Sandra Pebrianti (LP4M STIKes Karsa Husada Garut, 2026)
Covid-19 is a disease caused by a corona virus that was first discovered in theprovince of Wuhan, the People's Republic of China and has become a globalpandemic. The virus attacks the respiratory system and causes mild disturbancesto death. The severity of the symptoms that appear is related to the state ofimmunity. The worse the immunity, the more susceptible to contracting Covid-19. In addition, individuals with poor immunity tend to experience severemanifestations of covid. Therefore, it is important to increase immunity duringthe Covid-19 pandemic. Efforts made to increase immunity include increasingcommunity capacity through community service activities in the form of awebinar entitled